A chromosome-level genome assembly of big-barbel schizothorcin, Schizothorax macropogon - Xuanguang Liang; Wenhao Wang; Junrou Huang; Mingfei Luo; Nima Wangdui; Caiyun Sun; Jianguo Lu (Scientific Data)
Abstract Big-barbel schizothorcin (Schizothorax macropogon), an endemic and vulnerable species to the mid-reaches of the Yarlung Zangbo River, epitomizes survival in harsh conditions yet suffers significant population contractions due to human activities. This species was the subject of our study in which we leveraged PacBio, MGI-Seq, and Hi-C data to assemble a chromosome-scale genome. This assembly comprises 25 pseudo-chromosomes, yielding a genome size of 1.42 Gb with a scaffold N50 length of 59.4 Mb, indicative of a highly contiguous assembly. A BUSCO assessment ascertained the comprehensiveness of the genome at 97.9%. Annotation efforts identified 46,246 putative protein-coding genes, with 49.61% of the assembled genome annotated as repetitive sequences. This genome assembly is instrumental for advancing conservation of the giant whiskered schizothoracines and related species, and for illuminating the evolution and ecology of schizothoracine fishes in the Qinghai-Tibet Plateau.